Бункер разбитых сердец - Казанцев Кирилл (Колычев рекомендует: бандитские страсти, 2016)
Экземпляры: ф.9 (20190216) / Инвентарный номер: 43304 / Цена: / Авт.знак: К 14 / ГРНТИ: 17.82.31 / ББК: 84 (2Рос=Рус)6-44